DIGITAL INNOVATIONS AND THE PRODUCTION OF LOCAL CONTENT IN COMMUNITY RADIO; CHANGING PRACTICES IN THE UK - Coleman, Josephine F. (ABINGDON : ROUTLEDGE, 2021)
This book offers an in-depth analysis of how local community radio practitioners have embraced the digital revolution. Digital Innovations and the Production of Local Content in Community Radio contextualizes the UK model of community radio, before focussing on specific case studies to examine how the use of digital technologies has affected local radio production practices. The book offers an overview of the new technologies, media forms, and platforms in radio production, shedding light on how digitalization is impacting the routines and experiences of a predominantly volunteer-based workforce. The author presents the argument that despite the benefits of digital media, traditional aspects of programme production continue to be of vital importance to the interpersonal relationships and values of community radio. This book will appeal to academics and researchers in the areas of communication, culture, journalism studies, media, and creative industries.
OCLC-licensed vendor bibliographic record.
Keywords: Community radio -- Great Britain -- Case studies; Community radio -- Technological innovations; LANGUAGE ARTS & DISCIPLINES / Journalism